Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3847/1538-4357/ab77b9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Heating and Cooling of the Interstellar Medium at High Redshift: PAH and [C ii] Observations of the Same Star-forming Galaxies at z ∼ 2

Abstract: Star formation depends critically on cooling mechanisms in the interstellar medium (ISM); however, thermal properties of gas in galaxies at the peak epoch of star formation (z ∼ 2) remain poorly understood. A limiting factor in understanding the multiphase ISM is the lack of multiple tracers detected in the same galaxies, such as Polycyclic Aromatic Hydrocarbon (PAH) emission, a tracer of a critical photoelectric heating mechanism in interstellar gas, and [C II] 158µm fine-structure emission, a principal coola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 111 publications
3
23
0
Order By: Relevance
“…wide distribution of the radiation field intensities, different optical depths, and source geometry). This is in line with results from studies that have explored the cosmic evolution of interstellar radiation fields and its complex link to galaxy stellar mass (Béthermin et al 2015;Schreiber et al 2018) or gas mass (Kirkpatrick et al 2017;McKinney et al 2020).…”
Section: Evolution Of M Dust −Sfr With Respect To the Mssupporting
confidence: 89%
“…wide distribution of the radiation field intensities, different optical depths, and source geometry). This is in line with results from studies that have explored the cosmic evolution of interstellar radiation fields and its complex link to galaxy stellar mass (Béthermin et al 2015;Schreiber et al 2018) or gas mass (Kirkpatrick et al 2017;McKinney et al 2020).…”
Section: Evolution Of M Dust −Sfr With Respect To the Mssupporting
confidence: 89%
“…This reinforces the link between the ejection of photoelectrons from PAH grains and the collisional excitation of [C II] and other fine-structure lines, and suggests that the heating and cooling processes within PDRs behave similarly for normal star-forming conditions over a range of T dust and L IR . Interestingly, McKinney et al (2020) found lower [C II]/PAH emission at z ∼ 2 than z ∼ 0, suggesting evolution in the heating and cooling balance with redshift. However, the cooling/heating ratio has yet to be fully characterized in z ∼ 0 starbursts, which represents a key step for future studies of the early universe.…”
Section: Introductionmentioning
confidence: 90%
“…Recent efforts to combine mid-and far-IR measurements of gas heating and cooling at z ∼ 1-2 are largely limited to handfuls of ULIRGs with archival Spitzer/IRS spectra (Brisbin et al 2015;McKinney et al 2020 II] as in local (U)LIRGs. If this is the case, then GS IRS20 would have a 3.3 μm PAH flux of 7 × 10 −17 W m −2 , which can be easily detected in under 15 minutes by the James Webb Space Telescope (JWST) Mid-Infrared Instrument (MIRI).…”
Section: Prospects For Star Formation At High Redshiftmentioning
confidence: 99%
“…Recent efforts to combine mid-and far-IR measurements of gas heating and cooling at z ∼ 1 − 2 are largely limited to handfuls of ULIRGs with archival Spitzer /IRS spectra (Brisbin et al 2015;McKinney et al 2020). Using ALMA, McKinney et al (2020) compared the [C II] and 6.2 µm PAH emission for GS IRS20, a luminous, compact starburst galaxy at z = 1.9239 and found a low [C II]/6.2 µm ratio at high IR surface density that could indicate a low photoelectric efficiency. This galaxy has a L [C II] /L 11.3 ratio of 0.11, which would correspond to a 11.3/3.3 µm ratio of 21.5 if z ∼ 2 galaxies follow similar scaling relations between the PAH features and [C II] as in local (U)LIRGs.…”
Section: Prospects For Star-formation At High-redshiftmentioning
confidence: 99%